The Effect of Insurance Status on Mortality and Procedural Use in Critically Ill Patients - Lyon, Sarah M. (American Thoracic Society, 2011)
Rationale: Lack of health insurance may be an independent risk factor for mortality and differential treatment in critical illness. Objectives: To determine whether uninsured critically ill patients had differences in 30-day mortality and critical care service use compared with those with private insurance and to determine if outcome variability could be attributed to patient-level or hospital-level effects. Methods: Retrospective cohort study using Pennsylvania hospital discharge data with detailed clinical risk adjustment, from fiscal years 2005 and 2006, consisting of 167 general acute care hospitals, with 138,720 critically ill adult patients 64 years of age or younger. Measurements and Main Results: Measurements were 30-day mortality and receipt of five critical care procedures. Uninsured patients had an absolute 30-day mortality of 5.7%, compared with 4.6% for those with private insurance and 6.4% for those with Medicaid. Increased 30-day mortality among uninsured patients persisted after adjustment for patient characteristics (odds ratio [OR], 1.25 for uninsured vs. insured; 95% confidence interval [CI], 1.04–1.50) and hospital-level effects (OR, 1.26; 95% CI, 1.05–1.51). Compared with insured patients, uninsured patients had decreased risk-adjusted odds of receiving a central venous catheter (OR, 0.84; 95% CI, 0.72–0.97), acute hemodialysis (OR, 0.59; 95% CI, 0.39–0.91), and tracheostomy (OR, 0.43; 95% CI, 0.29–0.64). Conclusions: Lack of health insurance is associated with increased 30-day mortality and decreased use of common procedures for the critically ill in Pennsylvania. Differences were not attributable to hospital-level effects, suggesting that the uninsured have a higher mortality and receive fewer procedures when compared with privately insured patients treated at the same hospitals.